In honorem Comenius: Array - Lates, Gheorghe (Didactica Danubiensis, 2022)
The cultural differences between nations have the immediate effect of different organizations. Globalization recommends and imposes a synchronization of them. At the end of the school year, a Comenius thought of an education system that humanity has implemented and still believes that it is the best teaching solution. The holy tradition of the school (with particular insistence) proves, at first glance, one that inhibits change, the same can be said about the reform.